2018
DOI: 10.1186/s13054-018-2159-x
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition feeding in Chinese intensive care units: a cross-sectional study involving 116 hospitals

Abstract: BackgroundThere is a lack of large-scale epidemiological data on the clinical practice of enteral nutrition (EN) feeding in China. This study aimed to provide such data on Chinese hospitals and to investigate factors associated with EN delivery.MethodsThis cross-sectional study was launched in 118 intensive care units (ICUs) of 116 mainland hospitals and conducted on April 26, 2017. At 00:00 on April 26, all patients in these ICUs were included. Demographic and clinical variables of patients on April 25 were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(26 reference statements)
1
13
0
1
Order By: Relevance
“…Furthermore, despite the existence of nutrition guidelines for the critically ill, observance of these guidelines remains poor [ 39 ]. In a cross-sectional study across China [ 40 ], EN was found to be suboptimal in ICUs and energy targets were poorly met during the early days of ICU stay. It is likely that early nutrition is still not prevalent in the ICU setting, and it needs to be implemented as an intervention to investigate its effect on physical functioning (including muscle strength, function, and muscle mass) [ 41 ] when applied alone compared to when implemented in EMN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the existence of nutrition guidelines for the critically ill, observance of these guidelines remains poor [ 39 ]. In a cross-sectional study across China [ 40 ], EN was found to be suboptimal in ICUs and energy targets were poorly met during the early days of ICU stay. It is likely that early nutrition is still not prevalent in the ICU setting, and it needs to be implemented as an intervention to investigate its effect on physical functioning (including muscle strength, function, and muscle mass) [ 41 ] when applied alone compared to when implemented in EMN.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that study, the patients in the present study achieved lower rates of feeding success; however, this is partly due to patients' withdrawals in that study, resulting in a reduction in the number of patients remaining in the trial. Another study indicated that enteral nutrient delivery was suboptimal in Chinese ICUs because of a lack of or differences in standardized feeding protocols, which may make it difficult to compare the present data with other studies [27]. However, we adopted a volume-based feeding strategy, with reduced energy and increased protein density, which is popular in our hospital, perhaps because of a fear of hyperglycemia.…”
Section: Discussionmentioning
confidence: 94%
“…The Working Group on Abdominal Problems of the European Society of Intensive Care Medicine firstly developed the definitions of AGI with four grades of severity, making it possible to estimate the gastrointestinal function of critically ill patients ( 20 ). AGI is widely used in ICU ( 21 , 22 ). A multi-prospective study that recruited patients admitted to ICU diagnosed with AGI showed that AGI grading was positively correlated with all-cause mortality ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%